Social innovation and impact in nonprofit leadership - Hansen-Turton, Tine; Torres, Nicholas D.; Alleva, Jennifer; Michal, Jill M.; Hunter, David E.; Berger, Ken.; Clark, Michael; Cohen, Richard; Carnesi, Mark.; Brenner, Sara.; Kim, Peter, 1974-; Wolfman, Dina.; et al. (New York : Springer Publishing Company, 2014)
This text encompasses the core competencies required to lead nonprofit organizations through social innovation and impact during the 21st century. It fills a knowledge gap for leaders, managers, practitioners, students, faculty members, and providers in this rapidly growing field by providing a comprehensive framework for how to run and manage nonprofits. This includes all of the tools needed to affect social change through ethical business practices, management and leadership business strategies, social marketing, and policy analysis across government, nonprofits, and philanthropy. The book addresses solutions to key problem for professionals in the nonprofit sector: creating a return on investment defined by concrete outcomes and ability to demonstrate their organization's impact. Organizational case studies are presented by practitioners who have used innovative principles to organize, create, and manage ventures to influence social change locally, regionally, and beyond.
Nonprofit accountability, transparency, governance, fiduciary responsibilities, and ethics / Jennifer Alleva, Jill M. Michal, Nicholas D. Torres -- Evaluating organizational impact and outcome measurement / David E.K. Hunter -- Outcomes as scaling platforms / Ken Berger [and four others] -- Next-generation nonprofits / Michael Clark [and five others] -- Convening, leading, and supporting the social sector : best and next practices / Richard Cohen [and three others] -- Generational leadership in leading social innovations and impact / Mark Carnesi [and five others] -- Death of planning--the birth of strategic action plans / Sara Brenner [and five others] -- Complex organizations in the nonprofit social sector / Richard Cohen [and three others] -- Finding your funding model : a practical approach to nonprofit sustainability / Peter Kim [and three others] -- Marketing and communication / Dina Wolfman Baker and Theodore Search -- Government contracting and how to navigate fiscal crisis / Daniel Stid, Willa Seldon, and the Urban Institutue -- Advocacy strategies for policy change / Tine Hansen [and three others].
Includes bibliographical references and index.
Keywords: Nonprofit organizations -- Management; Leadership; Leadership; Nonprofit organizations -- Management